WLE/Alliance-supported data sharing and big data applications being rolled out in Ethiopia to encourage the government's efforts to transform agriculture - CGIAR Research Program on Water, Land and Ecosystems (2020)
A collaborative effort by WLE/Alliance, GIZ-Ethiopia and partners to institutionalize data sharing has led the Ethiopian Ministry of Agriculture to adopt the concept. Partners undertook many activities: creation of a digital web portal, data collation, standardization guidelines and big data analysis. They are now developing a site-specific fertilizer recommendation tool. This has led to better-targeted recommendations and a paradigm shift in the research and development discourse as well as further funding and scaling of the framework to other countries.